STRUKTUR DAN BENTUK GENDING IRINGAN REOG PONOROGO - Faisol Amir; Bondet Wrahatnala (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2022)
Reog Ponorogo is a traditional dance that developed in Ponorogo, East Java. The presentation cannot be separated from the music as one of the determining factors for the success of performances. This study aims to describe the structure and form of the Reog Ponorogo gending. The Qualitative research methods that using observation and interview techniques are used to support the data collection process in this study. In its presentation, Reog Ponorogo has standard music (pakem) according to the movement of the characters being played. The gending form of used has a simple colotomic structure with name obyog, patrajayan, ponoragan, sampak and kebogiro. Based on the structure, some of gending have a similarities and different of rhythm, laya and garap/ improvisation. As a traditional performing arts, the gending of Reog Ponorogo has been agreed (conventionally) by the community, one of which is the application of gending in each dance fragment. Gending obyok, ponoragan and sampak have a wider application, namely in all dance fragments even though the different intensity. Meanwhile, gending kebo giro only appears and becomes the main accompaniment of the Bujang Ganong and Klana Sewandana fragments.